Along came a duke - Boyle, Elizabeth (New York, N.Y. : Avon Books, 2012)
In order to claim a vast fortune, Tabitha Timmons, a penniless spinster, must marry the very respectable Mr. Barkworth, but finds herself torn between the good fortune that guarantees her security and her feelings for the Duke of Preston, who vows to save her from a passionless union.
Includes an excerpt from the next book in Elizabeth Boyle's Rhymes with love series.
Keywords: Aristocracy (Social class) -- Fiction; London (England) -- History -- Fiction; Inheritance and succession -- Fiction; Orphans -- Fiction; Single women -- Fiction; Bachelors -- Fiction; Nobility -- Fiction; Forced marriage -- Fiction; Love stories; Historical fiction